2005
DOI: 10.1108/13598540510578379
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for supply chain management: a structural integration

Abstract: Purpose-The main purpose of this paper is to document the research on development of a conceptual framework for the supply chain. The aims of the research were to develop an integrated framework, and to provide a methodology for planning of many components in the supply chain such as suppliers, materials, resources, warehouses, activities and customers. The proposed framework is based on the unitary structuring technique where bills of materials, bills of warehouses, project networks and operations routings, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 9 publications
0
57
0
3
Order By: Relevance
“…Other researchers (e.g., Closs and Mollenkopf 2004;Janvier-James 2012;Lambert, Cooper, and Pagh 1998;Samaranayake 2005;Spens and Bask 2002) have focused on this issue from both theoretical and empirical perspectives. However, in many of these studies, the focus has been on issues such as process, investments, and structure without an overall framework that ties these aspects together.…”
Section: Supply Chain Design -Defining the Conceptmentioning
confidence: 99%
“…Other researchers (e.g., Closs and Mollenkopf 2004;Janvier-James 2012;Lambert, Cooper, and Pagh 1998;Samaranayake 2005;Spens and Bask 2002) have focused on this issue from both theoretical and empirical perspectives. However, in many of these studies, the focus has been on issues such as process, investments, and structure without an overall framework that ties these aspects together.…”
Section: Supply Chain Design -Defining the Conceptmentioning
confidence: 99%
“…Accordingly, some studies have suggested including supply chain relationships as a fourth dimension, in addition to the three flows (e.g., Power, 2005;Samaranayake, 2005). The industrial network approach, which is used increasingly in logistics and supply chain management studies (e.g., Håkansson and Persson, 2004, Bygballe, 2006, Awaleh, 2008, placed the relationships in the centre, suggesting they are based on how business units are connected through three layers.…”
Section: Figure 1: Horizontal and Vertical Cooperation (Source: Barramentioning
confidence: 99%
“…O Global Supply Chain Fórum -GSCF, conforme relatam Lambert e Cooper (2000) e Croxton et al (2001), identificou oito processos de negócios-chave para a configuração da cadeia, que se assemelham aos levantados por Samaranayake (2005), são eles: (i) processo de gestão do relacionamento com o consumidor; (ii) processo de gestão do serviço ao consumidor; (iii) processo de gestão da demanda; (iv) processo de cumprimento das ordens dos clientes; (v) processo de gestão do fluxo de produção; (vi) processo gestão do relacionamento com o fornecedor; (vii) processo de desenvolvimento e comercialização; e, (viii) processo de retorno. Existem alguns componentes de gestão comuns a todos os elos, a gestão destes determina o curso de ação dos negócios e a forma como a cadeia de suprimento é gerenciada e organizada.…”
Section: Quadro Teóricounclassified